Effect of corporate social responsibility and institutional ownership of tax avoidance with executive characters as moderator - Putra, I Gusti Bagus Wahyu Palguna; Sujana, I Ketut; Suprasto, Herkulanus Bambang; Gayatri, Gayatri (International research journal of management, IT and social sciences, 2019)
This study aims to obtain empirical evidence regarding the moderation of executive characteristics on the influence of corporate social responsibility and institutional ownership on tax avoidance. In the previous research, it was found that there were inconsistencies in the results of the research so that it was suspected that there were other variables that could influence the relationship between variables. In this study executive, characteristic variables are thought to moderate the relationship of corporate social responsibility and ownership structure in tax avoidance. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period of 2013-2017 as many as 150 companies. The sample collection technique uses purposive sampling. The number of samples in this study was 520 observation companies from 2013 to 2017. The data analysis technique used for moderation testing was Moderated Regression Analysis (MRA). The test results show that executive characteristics do not moderate the relationship of corporate social responsibility to tax avoidance and the characteristics of executive risk-takers weaken the relationship of institutional ownership to tax avoidance.